Peningkatan Keterampilan Berbicara Bahasa Inggris Dengan Metode Storytelling Di SMK Budi Utomo Binjai Tahun 2022 - Rudi Purwana; Mariana Mariana; Asrul Asrul; Afina Muharani Syaftriani; Ani Rahmadhani Kaban (BADAN PENERBIT STIEPARI PRESS, 2022)
This study investigates the enhancement of English speaking skills through the storytelling method at SMK Budi Utomo Binjai in 2022. The research aims to determine the effectiveness of storytelling as a pedagogical tool in improving students' verbal communication abilities in English. Employing a qualitative approach, data were collected through observations, interviews, and tests administered before and after the intervention. Findings indicate a significant improvement in students' speaking skills, with notable advancements in fluency, vocabulary usage, and confidence. The storytelling method proved to be an engaging and effective strategy, fostering a more interactive and participatory classroom environment. These results suggest that incorporating storytelling into language learning curricula can significantly enhance students' speaking proficiency, offering valuable implications for educators seeking innovative approaches to teaching English.